2018
DOI: 10.1038/s41431-017-0055-5
|View full text |Cite
|
Sign up to set email alerts
|

Homozygous deletion in MYL9 expands the molecular basis of megacystis–microcolon–intestinal hypoperistalsis syndrome

Abstract: Megacystis-microcolon-intestinal hypoperistalsis syndrome (MMIHS) is a severe disease characterized by functional obstruction in the urinary and gastrointestinal tract. The molecular basis of this condition started to be defined recently, and the genes related to the syndrome (ACTG2-heterozygous variant in sporadic cases; and MYH11 (myosin heavy chain 11), LMOD1 (leiomodin 1) and MYLK (myosin light chain (MLC) kinase)-autosomal recessive inheritance), encode proteins involved in the smooth muscle contraction, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
53
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(58 citation statements)
references
References 32 publications
3
53
0
2
Order By: Relevance
“…One of the key insights of our study is the central role that ACTG2 mutations and particularly arginine missense substitutions play in this spectrum of disease. Previously, evidence from some cohorts had also pointed to this predominant role for this locus in MMIHS (Ravenscroft et al, ), however, others have suggested that MMIHS is mostly an autosomal recessive disorder and that consanguinity is a major genetic risk factor (Nakamura et al, ) and indeed a number of recessive loci have been described (Gauthier et al, ; Halim, Brosens, et al, ; Halim, Wilson, et al, ; Moreno et al, ). Our cohort included four families with affected siblings and three with consanguinity, but interestingly, one of these cases was ultimately explained by the dominant inheritance of an ACTG2 variant with incomplete penetrance in the mother.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the key insights of our study is the central role that ACTG2 mutations and particularly arginine missense substitutions play in this spectrum of disease. Previously, evidence from some cohorts had also pointed to this predominant role for this locus in MMIHS (Ravenscroft et al, ), however, others have suggested that MMIHS is mostly an autosomal recessive disorder and that consanguinity is a major genetic risk factor (Nakamura et al, ) and indeed a number of recessive loci have been described (Gauthier et al, ; Halim, Brosens, et al, ; Halim, Wilson, et al, ; Moreno et al, ). Our cohort included four families with affected siblings and three with consanguinity, but interestingly, one of these cases was ultimately explained by the dominant inheritance of an ACTG2 variant with incomplete penetrance in the mother.…”
Section: Discussionmentioning
confidence: 99%
“…Autosomal recessive forms of MMIHS are caused by biallelic loss‐of‐function variants in other proteins involved in actin–myosin interactions: MYH11 (myosin‐heavy chain; Gauthier et al, ), MYLK (myosin‐light chain kinase; Halim, Brosens, et al, ), LMOD1 (leiomodin 1, an actin‐binding protein expressed primarily in vascular and visceral smooth muscle; Halim, Wilson, et al, ) and MYL9 (regulatory myosin‐light chain; Moreno et al, ). Other genes that are implicated in intestinal hypoperistalsis, but usually with other distinguishing phenotypic features include genes causing mitochondrial disorders ( TYMP and POLG ); EDNRB, EDN3 , and SOX10 associated with Waardenburg syndrome with Hirschsprung disease; SGOL1 , RAD21 , FLNA , and L1CAM .…”
Section: Introductionmentioning
confidence: 99%
“…Secondly, population‐based analysis with large cohort size or family‐based analysis may be preferred to increase statistical power. Family studies especially have proved to be an effective way of gene discovery in rare diseases as shown by our identification of a MYH11 pathogenic variant and previous reports of homozygous variants in consanguineous families . Thus, future studies investigating segregated dominant variants in large CIPO families with multiple affected individuals or homozygotes from consanguineous families may be cost‐effective.…”
Section: Discussionmentioning
confidence: 99%
“…It is one of the contractile apparatus components and pathogenic variants in the protein impair its polymerization and result in the reduced cellular contractility . Additionally, homozygous mutations in MYLK , MYH11 , LMOD1 , MYL9 , and RAD21 and X‐linked mutation in FLNA have been found in a small number of cases. Moreover, compound‐heterozygous mutations in MYH11 have also been reported in two CIPO families .…”
Section: Introductionmentioning
confidence: 99%
“…Although dilated pupils are present in all affected individuals reported to date with biallelic CHRM3 variants indicating that this is a core feature of the phenotype, the association of bladder dysfunction with mydriasis is not exclusive to individuals with CHRM3 variants. Of note individuals with biallelic pathogenic variants in MYL9 have mydriasis as part of megacystis microcolon intestinal hypoperistalsis phenotype . The similarity in the bladder‐eye phenotype in the two families would indicate that the missense variant results in a loss of function comparable to that predicted by the frameshift variant identified by Weber et al It will be important through murine and cellular studies to undertake functional studies to determine the mechanism of action of the reported disease‐associated variants.…”
Section: Discussionmentioning
confidence: 96%